Association of Dipeptidyl Peptidase-4 Inhibitor Use and Amyloid Burden in Patients With Diabetes and AD-Related Cognitive Impairment. (14th September 2021) - Jeong, Seong Ho; Kim, Hye Ryun; Kim, Jeonghun; Kim, Hankyeol; Hong, Namki; Jung, Jin Ho; Baik, Kyoungwon; Cho, Hanna; Lyoo, Chul Hyoung; Ye, Byoung Seok; Sohn, Young H.; Seong, Joon-Kyung; et al.
Abstract : Background and Objective: To investigate whether dipeptidyl peptidase-4 inhibitors (DPP-4i) have beneficial effects on amyloid aggregation and longitudinal cognitive outcome in diabetic Alzheimer disease–related cognitive impairment (ADCI). Methods: We retrospectively reviewed 282 patients with ADCI with positive 18 F-florbetaben amyloid PET images. Patients were classified into 3 groups according to prior diagnosis of diabetes and DPP-4i use: diabetic patients being treated with (ADCI-DPP-4i +, n = 70) or without DPP-4i (ADCI-DPP-4i −, n = 71) and nondiabetic patients (n = 141). Multiple linear regression analyses were performed to determine intergroup differences in global and regional amyloid retention using standardized uptake value ratios calculated from cortical areas. We assessed longitudinal changes in Mini-Mental State Examination (MMSE) score using a linear mixed model. Results: The ADCI-DPP-4i + group had lower global amyloid burden than the ADCI-DPP-4i − group (β = 0.075, SE = 0.024, p = 0.002) and the nondiabetic ADCI group (β = 0.054, SE = 0.021, p = 0.010) after adjusting for age, sex, education, cognitive status, and APOE ε4 carrier status. The ADCI-DPP-4i + group had lower regional amyloid burden in temporo-parietal areas than either the ADCI-DPP-4i − group or the nondiabetic ADCI group. The ADCI-DPP-4i + group showed a slower longitudinal decrease in MMSE score (β = 0.772, SE = 0.272, p = 0.005) and memory recall subscore (β = 0.291, SE = 0.116, p = 0.012) than the ADCI-DPP-4i − group. Discussion: These findings suggest that DPP-4i use is associated with low amyloid burden and favorable long-term cognitive outcome in diabetic patients with ADCI.